The links between dietary diversity and RNA virus diversity harbored by the great evening bat (Ia io) - Zhenglanyi Huang; Zhiqiang Wang; Yingying Liu; Can Ke; Jiang Feng; Biao He; Tinglei Jiang (Microbiome)
Abstract Background Predator‒prey interactions and their dynamic changes provide frequent opportunities for viruses to spread among organisms and thus affect their virus diversity. However, the connections between dietary diversity and virus diversity in predators have seldom been studied. The avivorous bats, Ia io, show a seasonal pattern of dietary diversity. Although most of them primarily prey on insects in summer, they mainly prey on nocturnally migrating birds in spring and autumn. Results In this study, we characterized the RNA virome of three populations of I. io in Southwest China during summer and autumn using viral metatranscriptomic sequencing. We also investigated the relationships between dietary diversity and RNA virus diversity by integrating DNA metabarcoding and viral metatranscriptomic sequencing techniques at the population level of I. io. We found 55 known genera belonging to 35 known families of RNA viruses. Besides detecting mammal-related viruses, which are the usual concern, we also found a high abundance of insect-related viruses and some bird-related viruses. We found that insect-related viruses were more abundant in summer, while the bird-related viruses were predominantly detected in autumn, which might be caused by the seasonal differences in prey selection by I. io. Additionally, a significant positive correlation was identified between prey diversity and total virus diversity. The more similar the prey composition, the more similar the total virus composition and the higher the count of potential new viruses. We also found that the relative abundance of Picornaviridae increased with increasing prey diversity and body mass. Conclusions In this study, significant links were found between RNA virus diversity and dietary diversity of I. io. The results implied that dynamic changes in predator–prey interactions may facilitate frequent opportunities for viruses to spread among organisms. Video Abstract